Astronomy: its uses past and present - Freeman, Ernest Harrison (My University, 1895)
Introduction: There are many who, knowing little of astronomy, regard it as a science without any practical uses. They think it a science of speculation and theories, and one which gives us no material aid in our struggle for higher civilization. In some aspects, this may be true; yet there is a practical side to astronomy which has been an important factor in past progress.
Citation: Freeman, Ernest Harrison. Astronomy: its uses past and present. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Astronomy; Science; Civilization; Theses; Manuscripts (documents)